Weak neutral current axial form factor using ν ¯ ν $$ \left(\overline{ν}\right)ν $$ -nucleon scattering and lattice QCD inputs - Raza Sabbir Sufian; Keh-Fei Liu; David G. Richards (Journal of High Energy Physics)
Abstract We present a determination of the neutral current weak axial charge G A Z 0 = − 0.654 3 stat 5 sys $$ G_A^Z(0)=-0.654{(3)}_{stat}{(5)}_{sys} $$ using the strange quark axial charge G A s 0 $$ G_A^s(0) $$ calculated with lattice QCD. We then perform a phenomenological analysis, where we combine the strange quark electromagnetic form factor from lattice QCD with (anti)neutrino-nucleon scattering differential cross section from MiniBooNE experiments in a momentum transfer region 0.24 ≲ Q2 ≲ 0.71 GeV2 to determine the neutral current weak axial form factor G A Z Q 2 $$ G_A^Z\left(Q^2\right) $$ in the range of 0 ≲ Q2 ≤ 1 GeV2. This yields a phenomenological value of G A Z 0 $$ G_A^Z(0) $$ = −0.687(89)stat(40)sys. The value of G A Z 0 $$ G_A^Z(0) $$ constrained by the lattice QCD calculation of G A s 0 $$ G_A^s(0) $$ , when compared to its phenomenological determination, provides a significant improvement in precision and accuracy and can be used to provide a constraint on the fit to G A Z Q 2 $$ G_A^Z\left(Q^2\right) $$ for Q2> 0. This constrained fit leads to an unambiguous determination of (anti)neutrino-nucleon neutral current elastic scattering differential cross section near Q2 = 0 and can play an important role in numerically isolating nuclear effects in this region. We show a consistent description of G A Z Q 2 $$ G_A^Z\left(Q^2\right) $$ obtained from the (anti)neutrino-nucleon scattering cross section data requires a nonzero contribution of the strange quark electromagnetic form factor. We demonstrate the robustness of our analysis by providing a post-diction of the BNL E734 experimental data.